Concentration of authority and rent seeking behaviour in bureaucracy: An evidence of ineffective governance in Bangladesh - Naim, Sayada Jannatun; Hasan, Abu Hena Reza (IDEAS, 2022)
This article was published in The Journal of Social and Development Sciences and the definite version is available at: http://DOI: 10.22610/jsds.v9i1.2165 The Article's website is at: https://ideas.repec.org/a/rnd/arjsds/v9y2018i1p19-30.html